Concordance of PD-L1 Status Between Image-Guided Percutaneous Biopsies and Matched Surgical Specimen in Non-Small Cell Lung Cancer - Zhao, Liang; Chen, Peiqiong; Fu, Kaili; Li, Jinluan; Dai, Yaqing; Wang, Yuhuan; Zhuang, Yanzhen; Sun, Long; Chen, Haojun; Lin, Qin (Frontiers in Oncology, 2021)
Objectives：Programmed death-ligand 1 (PD-L1) expression status is a crucial index for identifying patients who will benefit from anti-programmed cell death protein 1 (PD-1)/PD-L1 therapy for non-small cell lung cancer (NSCLC). However, the concordance of Tumor Proportion Score (TPS) between biopsies and matched surgical specimens remains controversial. This study aims too evaluate the concordance of PD-L1 expression between image-guided percutaneous biopsies and matched surgical specimens. Methods：We evaluated 157 patients diagnosed with operable NSCLC on both surgical tissue sections and matched lung biopsies retrospectively. The patients underwent either regular computed tomography (CT)-guided biopsy (n=82) or positron emission tomography (PET)/CT-guided biopsy (n=75). The concordance between surgical specimens and lung biopsies for PD-L1 TPS was evaluated using Cohen’s kappa (κ) coefficient. Results：Immunohistochemical expression of PD-L1 was evaluated in both surgical resected specimens and matched biopsies in the eligible 138 patients. The concordance rate of PD-L1 expression between surgical tissue sections and matched biopsies was fairly high at 84.1% (116/138), and the κ value was 0.73 (95% CI: 0.63–0.83, P<0.001). The concordance rate was higher for tissue sections from PET/CT-guided biopsy than for tissue sections from CT-guided biopsy (88.6% [62/70, κ value: 0.81] vs 79.4% [54/68, κ value: 0.66]). Conclusion：PD-L1 TPS was strongly concordant between surgical specimens and matched lung biopsies. Thus, the routine evaluation of PD-L1 expression in diagnostic percutaneous biopsies could be reliable for identifying patients who will benefit from anti-PD-1/PD-L1 immunotherapy.